KESALAHAN EJAAN BAHASA INDONESIA PADA TEKS UNDANG-UNDANG MAHASISWA UNIVERSITAS RIAU NOMOR 3 TAHUN 2018 - Fahronnisya, Novia; Sinaga, Mangatur; Burhanudin, Dudung (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study is to examine spelling errors that include the use of capital letters, the use of italics, and the use of punctuation punctuation marks contained in the University of Riau Student Act Number 3 of 2018 based on the rules that apply to the General Spelling of Language Guidelines Indonesia. Based on the data analysis that has been done, the use of capital letters that are not in accordance with the Indonesian Spelling rules in the text of the University of Riau Student Law Number 3 Year 2018 found 41 cases which included 18 writing errors in the names of positions and ranks, errors in writing names of institutions and 14 writing errors in the name of official documents, and 8 errors in the acronym of self-name consisting of a combination of the initial letters of each word and a combination of syllables. Furthermore, 11 oblique use errors in the writing of words or expressions in regional or foreign languages, 19 errors in the use of dots at the end of the sentence, and 20 errors in the use of semicolon punctuation at the end of the detail in the form of clauses. Key Words: Indonesian Language spelling errors, the text of the law students of the University      of Riau number 3 Year 2018.